ESTUDOS DE GENETICA HUMAN EM AREAS DE ALTA RADIACAO NATURAL. VII. CARGA GENETICA - Freire Maia, A. (My University, 1975)
Two methods to estimate the inbreeding load are reviewed. Both are employed in the analysis of our data. Besides the total population, a sample constituted of individuals with no alien ancestors is also analysed. No clear effect of natural radioactivity, as measured by genetic load models, has been found (this is especially valid for abortions, pre natal mortality, anomalies, and abnormalities in general). The results on stillbirths and post natal and total mortalities are discussed, and it is concluded that most probably the differences found are due to uncontrolled concomitant variables (if not to chance alone). Further analyses are under way.
Human genetics studies in areas of high natural radiation. VII. Genetic load